Analisis Media Sosial, Content Marketing Dan E-Wom Marketing Terhadap Keputusan Pembelian Pada UMKM Ritel di Desa Cikeas Udik – Bogor - Syamsudin Baharsyah; Rizky Muyasar (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2026)
Background – Social Media, Content Marketing, and e-WOM Marketing are factors that influence purchasing decisions. To prove the existence of this influence, this study was conducted with the aim of knowing and analyzing the role of Social Media, Content Marketing, and e-WOM Marketing simultaneously on purchasing decisions in retail MSMEs in Cikeas Udik Village, Bogor. This study was conducted in Cikeas Udik Village, Gunung Putri District, Bogor Regency, West Java Province, Indonesia by determining a number of respondents, namely consumers who make purchases at retail MSMEs. Aim – This study aims to determine how big the impact of Social Media, Content Marketing and e-WOM Marketing is on Purchasing Decisions in retail MSMEs in Cikeas Udik Village - Bogor. Design / methodology / approach – This study employed a non-probability approach with a purposive sampling technique. The analysis employed multivariate analysis with correlation or multiple regression. The sample size for this study was 46 respondents. The data collection method employed was to ask consumers who made purchases at retail MSMEs in Cikeas Udik Village to complete a questionnaire. Data were analyzed using SPSS version 26 for Windows. Findings – This research has produced findings including: Social Media, Content Marketing and e-WOM Marketing have influenced 58.4% of Purchasing Decisions in retail MSMEs in Cikeas Udik Village, Bogor. Conclusion - Based on the data analysis, it can be concluded that social media, content marketing, and e-WOM marketing have a positive and significant influence on purchasing decisions. Retail MSMEs in Cikeas Udik Village need to increase the role of social media, content marketing, and e-WOM marketing to increase the number of customers making purchasing decisions. Research implication – The research results are expected to describe objective conditions and produce accurate data. This can then serve as a guide for retail MSMEs to increase revenue and develop their businesses. Limitations – The limitation in this research is that it is part of a digital marketing strategy with the strategy of the role of social media, content marketing and e-WOM marketing being the main focus of the discussion, which is collaborated with purchasing decisions.